Extended peptide-based inhibitors efficiently target the proteasome and reveal overlapping specificities of the catalytic beta-subunits. - Kessler, B; Tortorella, D; Altun, M; Kisselev, A; Fiebiger, E; Hekking, BG; Ploegh, H; Overkleeft, H (2001)
BACKGROUND: The 26S proteasome is responsible for most cytosolic proteolysis, and is an important protease in major histocompatibility complex class I-mediated antigen presentation. Constitutively expressed proteasomes from mammalian sources possess three distinct catalytically active species, beta1, beta2 and beta5, which are replaced in the gamma-interferon-inducible immunoproteasome by a different set of catalytic subunits, beta1i, beta2i and beta5i, respectively. Based on preferred cleavage of short fluorogenic peptide substrates, activities of the proteasome have been assigned to individual subunits and classified as 'chymotryptic-like' (beta5), 'tryptic-like' (beta2) and 'peptidyl-glutamyl peptide hydrolyzing' (beta1). Studies with protein substrates indicate a far more complicated, less strict cleavage preference. We reasoned that inhibitors of extended size would give insight into the extent of overlapping substrate specificity of the individual activities and subunits. RESULTS: A new class of proteasome inhibitors, considerably extended in comparison with the commonly used fluorescent substrates and peptide-based inhibitors, has been prepared. Application of the safety catch resin allowed the generation of the target compounds using a solid phase protocol. Evaluation of the new compounds revealed a set of highly potent proteasome inhibitors that target all individual active subunits with comparable affinity, unlike the other inhibitors described to date. Modification of the most active compound, adamantane-acetyl-(6-aminohexanoyl)(3)-(leucinyl)(3)-vinyl-(methyl)-sulfone (AdaAhx(3)L(3)VS), itself capable of proteasome inhibition in living cells, afforded a new set of radio- and affinity labels. CONCLUSIONS: N-terminal extension of peptide vinyl sulfones has a profound influence on both their efficiency and selectivity as proteasome inhibitors. Such extensions greatly enhance inhibition and largely obliterate selectivity towards the individual catalytic activities. We conclude that for the interaction with larger substrates, there appears to be less discrimination of different substrate sequences for the catalytic activities than is normally assumed based on the use of small peptide-based substrates and inhibitors. The compounds described here are readily accessible synthetically, and are more potent inhibitors in living cells than their shorter peptide vinyl sulfone counterparts.